Neutraliza la verdad de una historia con la verdad de otra. The Rewriting of the Myth from Compassion in "Medea" (2020), by Chantal Maillard - Castillo Bel, Laura (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Medea is considered one of the most controversial characters in literature. Her first appearance in literature in Hesiod’s Theogony (957-962) has been followed by numerous others among classical and modern authors. Chantal Maillard is one of the poets who belongs to the long line of authors fascinated by this figure. The Belgian-Spanish poet rewrites the myth of Medea by placing at the centre the theme of compassion, which structures both her Medea (2020) and her essay entitled La compasión difícil (2019). Drawing on the principles of Feminist Myth-criticism by authors such as Estella Lauter, Barbara Godard, Donna Haraway, and the recent proposal by González Gil regarding the modes of intertwining that occur between the mythical subject and the poetic subject in contemporary Spanish poetry, this article analyses Maillard’s avant-garde reading of the myth of the already stereotypical filicide.